THE ROLE AND SIGNIFICANCE OF JADIDIST MOVEMENTS IN THE DEVELOPMENT OF LITERATURE OF THE CURRENT PERIOD (International journal of artificial intelligence, 2024)
This article provides a scientific and philosophical and didactic analysis of ideological ideas and their place in the current literature, which arose from the point of view of the periods, stages and structure of jadid literature. The importance of their works in the development of literature. This article analyzes the current problems of the XIX-XX centuries, the actions of representatives of jadid literature to eliminate these problems, the product of actions and the results.